EVALUATING GERIATRIC PRACTICES AMONG HOSPITAL NURSES: LESSONS FROM DISSEMINATION AND IMPLEMENTATION SCIENCE. (11th November 2018) - Rosenfeld, P; Lopez, M
Abstract: The Geriatric Resource Nurse (GRN) model, one exemplar of the national Nurses Improving Care for Healthsystem Elders (NICHE) program, seeks to improve eldercare practices in health care organizations through nurse-specific educational and training programs centered on evidence-based practice (EBP), interprofessional collaboration and quality improvement. This academic medical center launched a GRN program in 2014 with 115 GRNs distributed across 14 inpatients and 12 specialty areas. A multi-method evaluation study including surveys, focus groups and semi-structured interviews found a range of misconceptions among non-GRN nurses, nurse managers (NMs) and other providers about GRN training, scope of practice, and span of influence. General familiarity of the program was widespread but, other than NMs, few could identify GRNs on their units by name or quality initiatives led by GRNs. Additionally, GRNs revealed formidable challenges to implementing the EBP and knowledge obtained in training. Training alone did not result in translation of EBP to effective practice change. Our experience underscores the importance of integrating elements of Dissemination and Implementation(D&I) science into program development efforts. D&I science posits that effective use of EBP and other innovative practices do not organically spread across institutions; they require a systematic approach to communicating and promoting standardized processes to implementing change. Frequently innovations and efforts at EBP die on the vine due to the absence of a well-grounded dissemination plan and/or insufficient attention paid to implementation fidelity. This presentation will examine key concepts from the field of D&I that could enhance the success of efforts to change practice.